An overview of mercury emissions by global fuel combustion: The impact of international trade. (November 2016) - Chen, G.Q.; Li, J.S.; Chen, B.; Wen, C.; Yang, Q.; Alsaedi, A.; Hayat, T.
Abstract: This study provides an overview of mercury emissions by global fuel combustion by compiling the detailed inventory as well as elaborating the impact of international trade. Based on the global fuel-related mercury emissions inventory covering 26 sectors in 186 economies for the year of 2010, systems multi-region input-output analysis is employed for the first time to investigate international trade's impact on mercury emissions induced by each economy. The estimated mercury emissions mainly contributed by coal burning are 859.12 t, approximately 30% of which are embodied in commodities transported to consumers in other economies via international trade. The emerging economies such as mainland China and India are the prominent net exporters of embodied mercury emissions while developed economies like Japan, Germany and the USA are the net importers, indicating that developed economies avoided a large amount of direct mercury emissions by transferring the production of emission-intensive commodities to developing economies. By integrating the direct emissions and the net trade effect, mainland China has the largest embodied mercury emissions, followed by the USA and India. This study verifies the significant role of international trade in drawing a holistic picture of global fuel-related mercury emissions. The findings also suggest that focusing on the atmospheric mercury pollution directly emitted by local producers in isolation may result in an absurd situation of "regional reduction at the cost of global rise". It is anticipated that the current study provides insights for forming a reasonable emission responsibility sharing mechanism and facilitating comprehensive abatement strategies.